PENERAPAN ISAK 335 DALAM REKONSTRUKSI LAPORAN KEUANGAN: ANALASIS KASUS MASJID RAUDHATUS SHOLIHIN SITUBONDO - Ardhiarisca, Oryza; Filliyanti, Della (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
. The purpose of this study is to analyze and reconstruct the financial statements of public sector organizations, especially in places of worship, namely the Raudhatus Sholihin Mosque in Situbondo Regency based on the ISAK 335 standard. The financial problem that occurred in the mosque was that the preparation of financial statements had not been implemented in accordance with the standard, namely ISAK 335. The mosque only made simple records. This research method is qualitative research. Research data were collected through observation, interviews and documentation. Data validity is using technical triangulation. The results of the study indicate that the application of ISAK 335 through the reconstruction of financial statements produces more structured, detailed, and accountable reports. The reconstructed reports include financial position, comprehensive income statements, changes in net assets, cash flows, and notes to the financial statements, so as to increase transparency to the congregation, and also to donors, and other stakeholders.